2006
DOI: 10.1159/000092042
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Macrosomia – A Continuing Obstetric Challenge

Abstract: Background: Macrosomic fetuses represent a continuing challenge in obstetrics. Objectives: We studied maternal risk factors of fetal macrosomia and maternal and infant outcome in such cases. Methods: A retrospective cohort study was carried out with a total of 26,961 singleton pregnancies between 1989 and 2001. Records of 886 mothers who gave birth to live born infants weighing ≧4,500 g were compared to those of 26,075 mothers with normal weight (<4,500 g) infants. Multiple regression analysis was used to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
1
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 28 publications
0
52
1
6
Order By: Relevance
“…1,2 Newborns with a low birth weight have increased risk for perinatal as well as adult morbidity and mortality, 2 whereas newborns with a high birth weight are at increased risk for several complications, such as shoulder dystocia, operative delivery, and birth canal lacerations. 3 High birth weight is also associated with increased risk during adulthood of type 2 diabetes and some types of cancer (for example, endometrial, breast, or prostate). 1,2,4,5 The effect of exercise training during the course of pregnancy on the newborn's birth weight is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Newborns with a low birth weight have increased risk for perinatal as well as adult morbidity and mortality, 2 whereas newborns with a high birth weight are at increased risk for several complications, such as shoulder dystocia, operative delivery, and birth canal lacerations. 3 High birth weight is also associated with increased risk during adulthood of type 2 diabetes and some types of cancer (for example, endometrial, breast, or prostate). 1,2,4,5 The effect of exercise training during the course of pregnancy on the newborn's birth weight is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors too found that prolonged gestation was a risk factor for ≥ 4500 g macrosomia (5). Specifically, a gestational age at delivery > 41 weeks was a risk factor for some (4) while for others it was a gestational age > 42 weeks (10).…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this discrepancy being the low prevalence of neonatal complications observed by some authors when birth weight was < 4500 g compared to ≥ 4500g (1,7,8). Prevalence of macrosomic babies weighing 4500 g or more varies between 0.5% and 3.4% worldwide (2,6,9,10). There are several complications of macrosomia.…”
Section: Introductionmentioning
confidence: 99%
“…Factors related to high birth weight include maternal diabetes, advanced maternal age, maternal height, BMI and weight gain during pregnancy as well as gestational age and the sex of the child. [4,5,6]. Postulated mechanisms for the association of leukemia and birth weight have included exposure to growth factors (eg IGF-1) related to somatic growth and leukemogenesis [7], possible common genetic mechanisms or higher cell numbers in larger individuals providing increased opportunity for genetic errors.…”
Section: Introductionmentioning
confidence: 99%